The Effect Of Price And Product Quality On Purchase Decisions With Customer Reviews As An Intervening Variable On Shopee E-Commerce - Irene Nathalia Setiawan; Bambang Heriawan; Rusdiana Permanasari; Willyanto Kartiko Kusumo (Community Engagement and Emergence Journal (CEEJ), 2026)
The presence of fast-growing digital technology facilitates the transfer of information and communication in order to be possible. There are even innovations created in order to facilitate buyers and sellers to act as a third party or intermediary in their online transactions, which is the marketplace. In the case of online transactions, the consideration of buyers to the price and quality of products plays an important role in making a purchase. The customer reviews posted in the internet had also been considered as one of the factors that influence customers in making purchases in the Shopee e-commerce website. The approach of quantitative research was applied in this study through the questionnaire survey that was distributed to 100 respondents through Slovin’s formula analyzed using SmartPLS 4.0 software. The main objective of this study is to assess the effect of price and quality of the product in purchase decision-making, wherein the customer review is the intervening variable in the Shopee e-commerce. The findings prove that there is a positive and significant effect of the price and quality of products in the results of research. The price and quality of products significantly affect the performance in a positive manner. The review of expectations also includes positive changes that occur due to consumer society in making improvements